Cryptogenic stroke: A diagnostic challenge - Yaghi, Shadi (Lippincott Williams & Wilkins, 2014)
Cryptogenic, or unexplained, stroke is present in about 30%–40% of ischemic stroke patients. Pursuing a stroke mechanism is important in such patients to better choose therapy to reduce the stroke recurrence risk. Intracranial vessel imaging and cardiac evaluation with transesophageal echocardiogram and outpatient cardiac monitoring may help identify the stroke mechanism. This article highlights the diagnostic yield of various tests in identifying a stroke mechanism in stroke patients whose initial diagnostic evaluation is negative, and the implications for treatment.